The Accuracy of the Violent Offender Identification Directive Tool to Predict Future Gun Violence - Wheeler, Andrew P. (Criminal justice and behavior, 2019)
We evaluate the Violent Offender Identification Directive (VOID) tool, a risk prediction instrument implemented within a police department to identify offenders likely to be involved with future gun violence. VOID uses a variety of static measures of prior criminal history that are available in police records management systems. The VOID tool is assessed for predictive accuracy by taking a historical sample and calculating scores for over 200,000 individuals known to the police at the end of 2012, and predicting 103 individuals involved with gun violence (either as a shooter or a victim) during 2013. Despite weights for the instrument being determined in an ad hoc manner, the VOID tool does very well in predicting involvement with gun violence compared with an optimized logistic regression and generalized boosted models. We discuss theoretical reasons why such ad hoc instruments are likely to perform well in identifying chronic offenders for all police departments.